Dynamics of gut microbiota during pregnancy in women with TPOAb-positive subclinical hypothyroidism: a prospective cohort study - Min Wu; Cheng Chi; Yuxi Yang; Shan Guo; Tianhe Li; Muqing Gu; Tingting Zhang; Huimin Gao; Ruixia Liu; Chenghong Yin (BMC, 2022)
Abstract Background Anti-thyroid peroxidase antibody (TPOAb) positivity can contribute to inhibit thyroxine synthesis. Gut microbiota can interact with metabolic or immune diseases. However, dynamics of gut microbiota from the second (T2) to the third trimester (T3) in women with TPOAb-positive/negative subclinical hypothyroidism (TPOAb+/TPOAb− SCH) have not been reported. Therefore, we aimed to evaluate whether gut microbiota can be potential therapeutic targets for managing TPOAb+ SCH. Methods In this single-center prospective cohort study, we observed gut microbiota dynamics by sequencing 16S rRNA from fecal samples collected in T2 (20-23+ 6 weeks) and T3 (28-33+ 6 weeks). TPOAb+/TPOAb− SCH were stratified depending on whether or not they used levothyroxine (LT4) during the pregnancy (LT4 +/LT4 −). Microbiome bioinformatics analyses were performed using QIIME2. The linear discriminant analysis effect size (LEfSe) was used for the quantitative analysis of biomarkers. Functional profiling was performed with PICRUSt2. Results Distinct gut microbiota dynamics from T2 to T3 were noted in the TPOAb− (n = 68) and TPOAb+ (n = 64) SCH groups. The TPOAb+ LT4 − group was characterized by enriched bacterial amplicon sequence variants (ASVs) of Prevotella in T2 and Bacteria, Lachnospirales, Lachnospiraceae, Blautia, and Agathobacter in T3 and by depleted ASVs of Gammaproteobacteria, Enterobacterales, and Enterobacteriaceae in T2 and Actinobacteriota, Coriobacteriia, Actinobacteria, Coriobacteriales, Bifidobacteriales, Bifidobacteriaceae, Bifidobacterium, Dorea formicigenerans, and Bifidobacterium longum in T3. The TPOAb+ LT4 + group was characterized by enriched bacterial ASVs of Blautia, Streptococcus salivarius, and Bifidobacterium longum in T3 and by depleted ASVs of Bacteroidota, Bacteroidia, Bacteroidales, and Prevotella in T2 and Agathobacter in T3. Moreover, we identified 53 kinds of metabolic functions that were mainly involved in sugar, lipid, and amino acid metabolism. Conclusions Our results indicated that low dynamics of gut microbiota composition and high dynamics of its metabolic function from T2 to T3 were associated with TPOAb+ SCH. We concluded that gut microbiota could be new targets for treatment of TPOAb+ SCH during pregnancy. Trial registration This study was retrospectively registered at the Chinese Clinical Trial Registry (registration number ChiCTR2100047175 ) on June 10, 2021.